Development of a tool for optimizing Vehicle Routing Problem - Hamani, Amir (FACULTE DES MATHEMATIQUES ET DE L’INFORMATIQUE DEPARTEMENT D’INFORMATIQUE, 2018)
Combinatorial optimization occupies a very important place in research operational, in discrete mathematics and computer science. The vehicle routing problem (VRP) is a combinatorial optimization and integer programming problem which asks "What is the optimal set of routes for a fleet of vehicles to traverse in order to deliver to a given set of customers?”. It generalizes the well-known travelling salesman problem (TSP).
Keywords: VRP, TSP, Routing, Heuristics, C Sharp.